2019
DOI: 10.1016/j.urolonc.2019.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Communicative aspects of decision aids for localized prostate cancer treatment – A systematic review

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 47 publications
2
34
0
Order By: Relevance
“…Many did not adhere to good practice guidance on providing information about the development, evidence used for the content, or reporting readability levels. This limited adherence to the quality criteria has also been found among existing DAs for patients with localized prostate cancer [7, 12]. Nevertheless, it is promising to see that most of the recently launched or updated DAs in our review (i.e., from 2017 onwards) have shown increased adherence to the IPDAS criteria (see Fig.…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Many did not adhere to good practice guidance on providing information about the development, evidence used for the content, or reporting readability levels. This limited adherence to the quality criteria has also been found among existing DAs for patients with localized prostate cancer [7, 12]. Nevertheless, it is promising to see that most of the recently launched or updated DAs in our review (i.e., from 2017 onwards) have shown increased adherence to the IPDAS criteria (see Fig.…”
Section: Discussionsupporting
confidence: 61%
“…In this systematic review, we identified 21 currently available patient DAs for early-stage breast cancer treatment, and critically reviewed their quality (as assessed by the IPDAS checklist [10]) and use of communicative aspects (as assessed by a communicative aspect checklist [12]). This review shows substantial variability in the quality of the DAs, with no existing DA meeting all of the internationally agreed IPDAS criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decision aids range from basic informational pamphlets to more sophisticated and interactive technology and internet-based tools. Despite considerable variability in the quality of decision aids and their adherence to criteria outlined in the International Patient Decision Aid Standards, 12,13 decision aids for localized prostate cancer and PSA screening are associated with improved decisional outcomes (eg, reduced decisional conflict and regret, improved knowledge, satisfaction, and perceptions of control). 12,[14][15][16] However, few empirically supported decision aids have been developed for mPCa, leaving men with mPCa with little evidence-based guidance for facilitating shared decision-making.…”
mentioning
confidence: 99%